Reading several texts of poetry from the perspective of poetry - حسێن, علی طاهر; Mahmud, Shno Mohamed (Sulaimani Journal for Humanities, 2019)
The title of this resesrch includes some poetic texts that are analysed according to the poitic elements . Since the old times , different definitions , interpretations , terminologies and concepts about poetic notion have been discussed and a question has been raised can all the poetic texts be categorised into poetic frame ? This research answers this question . The research is devided into two chapters and it contains an Arabic and English abstract as well. First chapter is dedicated to the terminologies , definition and the poetic concepts . Also in the second chpter practicing some texts were taken as a sample .